Accumulation of gallium (Ga) and indium (In) in rice grains in Ga- and In-contaminated paddy soils. (June 2020) - Syu, Chien-Hui; Chen, Pei-Wen; Huang, Chia-Chen; Lee, Dar-Yuan
Abstract: To understand the risk of two emerging contaminants, gallium (Ga) and indium (In) to humans via rice consumption, effects of soil properties and concentrations of spiked Ga/In on the accumulation of Ga and In in rice grains were investigated. A pot experiment was conducted, and paddy rice was grown in three soils with different pH values and Al availabilities (i.e., Pc, TWz and Cf), which were spiked with various Ga and In concentrations. The growth index and concentrations of Ga, In, and Al in plant tissues and soil pore water were measured. Results revealed that the concentrations of Ga and In in soil pore water increase with the spiking of Ga or In in all of the tested soils, but the biomass of roots and shoots does not significantly decrease. The accumulation of Ga in shoots and brown rice was significantly reduced in high available Al acidic soils (Pc soils), but this accumulation was significantly increased in low available Al acidic soils (TWz soils), which can be explained by the competitive uptake between Ga and Al by rice plants. The extent of competitive effects between In and Al was less than that between Ga and Al because of the lower solubility and translocation capability of In than those of Ga in soil–rice systems. However, significant differences in the concentrations of Ga and In in brown rice in neutral soils (Cf soils) among the Ga or In treatment were not observed. In addition, the iron plaque formed on the root surface can serve as a barrier to reduce the accumulation of Ga in rice plants. This study suggested that the risk of accumulation of Ga and In in rice grains should be of concern when paddy rice is grown in acidic Ga- or In-contaminated soils with low Al availability. Graphical abstract: Image 109603 Highlights: Rice yield could be decreased by Ga and In treatments in acidic soils with low Al availability. Ga and In in rice grain is strongly related to the Al availability in acidic soils. No significant differences in Ga and In in brown rice in neutral soils. Concentrations of Ga in brown rice is much higher than In. Abstract : The accumulation of Ga and In in rice grains could be utilized for the risk exposure evaluation of Ga and In to humans via rice consumption.